ACL ruptures in competitive skiers: Biceps femoris fascicle lengths and pennation angles of the injured and non-injured limb several years following surgery - Tilp, M.; Schrettner, A.; Konrad, A.; Kruse, A.; Fischer, J.; Manieu, J.; Habersack, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Even years following ACL surgeries, hamstrings show reduced muscle activity and strength which are risk factors for relapsing injuries. A recent meta-analysis by Sherman et al. (2021) additionally reported structural changes like reduced muscular volume, cross-sectional area, and muscle length. Only one study (Timmins et al. 2016) investigated possible differences in fascicle lengths of the biceps femoris between ACL-injured and non-injured limbs of athletes. Estimates based on extrapolating visible parts of fascicles from ultrasound images revealed reduced total fascicle lengths and increased pennation angles in ACL-injured legs of rugby players. As the extrapolation of visible fascicles to obtain fascicle length is problematic (Franchi et al., 2021), the aim of the study was to compare fascicle lengths and pennation angles of the biceps femoris between ACL-injured and non-injured limbs of athletes by using extended field of view (EFOV) ultrasound to overcome this shortcoming. METHODS: Eight competitive skiers (2 males, 22.0 years, 173.6 +/- 5.7 cm, 69.6, +/- 6.7 kg) with a previous ACL surgery (4.1 +/- 3.4 years ago) gave their written confirmed consent to participate in the study. Biceps femoris fascicle lengths and pennation angles to the intermediate aponeurosis were measured in the ACL-injured and non-injured limb in a resting position using EFOV ultrasound (Aixplorer, Supersonic Imaging). Due to not normally distributed data, Wilcoxon tests were applied to test for possible differences between the ACL-injured and non-injured limb. RESULTS: Pilot data analyses revealed no significant differences in biceps femoris fascicle architecture between the ACL-injured and the non-injured limb. Fascicle lengths were 9.71+/-2.47 cm for the ACL-injured and 9.68 +/- 1.30 cm (p=0.67) for the non-injured leg. Pennation angles were 8.03 +/- 1.92° for the ACL-injured and 10.65 +/- 0.53° (p=0.06) for the non-injured leg. CONCLUSION: Four years following the ACL surgery, biceps femoris fascicle lengths and pennation angles were not significantly different between the ACL-injured and non-injured limb in competitive skiers. This result is in contrast to previous research that reported shorter fascicle lengths and greater pennation angles 3.5 years following an ACL surgery in rugby players (Timmins et al. 2016). Differences could be due to ultrasound fascicle measurement technique (Franchi et al., 2021) but also due to surgery technique, rehabilitation procedures, and/or participants characteristics. We recommend that future research should incorporate advanced 3D techniques and homogenous and stratified participant groups based on sex and surgical technique to thoroughly investigate potential structural alterations in fascicle architecture post-ACL surgery and their relation to functional deficits.